Pertumbuhan dan Hasil Tanaman Terung Ungu Varietas Yumi F1 dengan Pemberian Berbagai Bahan Organik dan Lama Inkubasi pada Tanah Berpasir - Titin Apung Atikah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
The research aims to study the response of plant purple eggplant F1 Yumi variety by providing various organic materials and the proper incubation duration on sandy soil. This research used Completely Randomized Factorial Design. The first factor is giving various organic materials (chicken manure, and kayambang bokashi manure + rice husk charcoal) and the second is the incubation duration (2.4 and 6 weeks before planting). The results showed that providing various organic materials and the incubation duration highly significant influence on plant height and number of leaves aged 4 and 6 weeks after planted, the number of productive branches and fresh weight of fruit crops, but did not significantly affect the parameters of plant height and number of leaves aged 2 WAP. The highest yield for plant height parameter aged 4 and 6 WAP, number of leaves aged 4 and 6 WAP, number of productive branchs, number of fruits and fresh fruit weight was obtained at bokashi manure + rice husk charcoal treatment with 4 weeks incubation duration before planting.